2022
DOI: 10.3390/neurosci3030037
|View full text |Cite
|
Sign up to set email alerts
|

How Do We Connect Brain Areas with Cognitive Functions? The Past, the Present and the Future

Abstract: One of the central goals of cognitive neuroscience is to understand how structure relates to function. Over the past century, clinical studies on patients with lesions have provided key insights into the relationship between brain areas and behavior. Since the early efforts for characterization of cognitive functions focused on localization, we provide an account of cognitive function in terms of localization. Next, using body perception as an example, we summarize the contemporary techniques. Finally, we outl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Despite unclear mechanisms underlying the therapeutic effects of rTMS on neurocognitive functions, previous studies have demonstrated an association of rTMS treatment with induction of dopamine release in the brain [ 15 ] and enhancement of synaptic neuroplasticity [ 16 , 17 ]. It is also well-reported that different regions of the brain are linked to various cognitive functions [ 34 ]; therefore, rTMS targeting specific brain regions to enhance a particular neurocognitive function seems a reasonable therapeutic approach [ 32 ]. Indeed, previous evidence suggested a stronger correlation of cognitive dysfunction with the right hemisphere compared to that on the left in patients with ADHD [ 35 , 36 ], highlighting the importance of investigating the possible influence of targeting different brain regions on the therapeutic efficacy of rTMS.…”
Section: Discussionmentioning
confidence: 99%
“…Despite unclear mechanisms underlying the therapeutic effects of rTMS on neurocognitive functions, previous studies have demonstrated an association of rTMS treatment with induction of dopamine release in the brain [ 15 ] and enhancement of synaptic neuroplasticity [ 16 , 17 ]. It is also well-reported that different regions of the brain are linked to various cognitive functions [ 34 ]; therefore, rTMS targeting specific brain regions to enhance a particular neurocognitive function seems a reasonable therapeutic approach [ 32 ]. Indeed, previous evidence suggested a stronger correlation of cognitive dysfunction with the right hemisphere compared to that on the left in patients with ADHD [ 35 , 36 ], highlighting the importance of investigating the possible influence of targeting different brain regions on the therapeutic efficacy of rTMS.…”
Section: Discussionmentioning
confidence: 99%